Competence-Based Readiness of Future Teachers to Professional Activity in Educational Institutions - Романюк, Світлана (My University, 2022)
The purpose of the scientific treatise is to investigate and intensify competence-based readiness of future teachers to professional activities in educational institutions, namely, the interrelated competencies of leaders’ communicationcompetence (LCC) and communication components of global competence (GC). To do this, jigsaw activities opinion sharing methods were applied to the educational environment of the students of the experimental group. In the process of achieving the goal of research the following methods were used: qualitative-quantitative and contrastive-comparative analysis of the obtained experimental data, statistical-mathematical interpretation of empirical data and their functional analysis, ascertaining experiment method and educational experiment method.The results of the educational experiment prove that on average the representatives of the experimental group managed to score 11.9 points more (9.6%) in accordance with the developed diagnostic paradigm of advanced communicative traits of modern teacher. The improvement of communicative competencies in the behaviour component was the most noticeable within the communication components of GC. The result is 10.0% higher in the experimental group, especially regarding the Skills component both within the LCC (10.3% higher in the experimental group) and within the communication components of GC (the difference here was 17.5%). The applied methods confirmed the positive effect on the development of vocationally orientated communicative competencies of student teachers.
Keywords: competence readiness; opinion sharing method; advanced communicative traits of modern teacher; leaders’ communication competence